HiPS‐Derived Astroglia Model Shows Temporal Transcriptomic Profile Related to Human Neural Development and Glia Competence Acquisition of a Maturing Astrocytic Identity. Issue 5 (6th April 2020) - Lundin, Anders; Ricchiuto, Piero; Clausen, Maryam; Hicks, Ryan; Falk, Anna; Herland, Anna
Abstract: Astrocyte biology has a functional and cellular diversity only observed in humans. The understanding of the regulatory network governing outer radial glia (RG), responsible for the expansion of the outer subventricular zone (oSVZ), and astrocyte cellular development remains elusive, partly since relevant human material to study these features is not readily available. A human‐induced pluripotent stem cell derived astrocytic model, NES‐Astro, has been recently developed, with high expression of astrocyte‐associated markers and high astrocyte‐relevant functionality. Here it is studied how the NES‐Astro phenotype develops during specification and its correlation to known RG and astrocyte characteristics in human brain development. It is demonstrated that directed differentiation of neurogenic long‐term neuroepithelial stem cells undergo a neurogenic‐to‐gliogenic competence preferential change, acquiring a glial fate. Temporal transcript profiles of long‐ and small RNA corroborate previously shown neurogenic restriction by glia‐associated let‐7 expression. Furthermore, NES‐Astro differentiation displays proposed mechanistic features important for the evolutionary expansion of the oSVZ together with an astroglia/astrocyte transcriptome. The NES‐Astro generation is a straight‐forward differentiation protocol from stable and expandable neuroepithelial stem cell lines derived from iPS cells. Thus, the NES‐Astro is an easy‐access cell system with high biological relevance for studies of mechanistic traits of glia and astrocyte. Abstract : Humans have unique features of astrocyte biology. Moreover, the structural development of the human cortex including outer subventricular zone radial glia cell development and contribution to astrocyte diversity remains elusive. This temporal expression study including mRNA, long non‐coding RNAs, micro RNAs, and protein demonstrate that the ltNES‐derived Astroglia model captures important developmental features strengthening it as developmental model with human translatability.